STUDENT CONCEPT UNDERSTANDING PROFILE ON ECOLOGY AND INDONESIA BIODIVERSITY MATERIAL BASED ON THE SELF-CONCEPT - Musayyaroh, Musayyaroh; Qomaria, Nur; Rakhmawan, Aditya; Ari Wahyuni, Eva; Hartiningsih, Try (Jurnal Pembelajaran Sains, 2024)
This study aims to determine students' conceptual understanding of ecology and Indonesia’s biodiversity materials from the perspective of students' self-concepts. The type of research used was quantitative descriptive. The study was carried out at SMPN 4 Bangkalan in the even semester of the 2023/2024 school year involving 50 research subjects of grade VII students. Data were collected through questionnaires and tests. The research findings indicate that: 1) The students' self-concept regarding science material shows that 10% of students were included in the high category, 28% in the moderate category, and 62% in the low category; 2) In the high self-concept group, the average concept understanding score was 69.64% with a good criterion, in the moderate self-concept group, the average concept understanding score was 49.23% with a sufficient criterion, and in the low self-concept group, the average concept understanding score was 23.92% with a poor criterion. Students with a high self-concept tend to have a good understanding of concepts related to ecology and biodiversity in Indonesia.